2019
DOI: 10.1155/2019/5925191
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Manifestations of Partial Agenesis of the Corpus Callosum: A Case Report and Literature Review

Abstract: Agenesis of the corpus callosum is a rare congenital defect that has been linked to psychiatric disorders, cognitive deficits, learning disabilities, and developmental delays. We present the case of a patient with partial agenesis of the corpus callosum who exhibits depressed mood, transient loss of memory, and history of cognitive, social, and behavioral disturbances that developed during his childhood. Recent and pertinent literature was reviewed and the agenesis of the corpus callosum and its associated neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 18 publications
(7 reference statements)
0
24
0
Order By: Relevance
“…While ACC has been previously described in patients with neuropsychiatric symptoms, the number of reports regarding corpus callosal malformation and psychosis remains limited and the underlying pathophysiologic mechanism is not well understood [3]. There is still no well-defined syndromic classification of corpus callosum pathologies, however, it has been associated with many chromosomal and metabolic disorders, CNS and somatic abnormalities, and intrauterine exposures to teratogens and infections [4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While ACC has been previously described in patients with neuropsychiatric symptoms, the number of reports regarding corpus callosal malformation and psychosis remains limited and the underlying pathophysiologic mechanism is not well understood [3]. There is still no well-defined syndromic classification of corpus callosum pathologies, however, it has been associated with many chromosomal and metabolic disorders, CNS and somatic abnormalities, and intrauterine exposures to teratogens and infections [4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…While the true prevalence of ACC may be difficult to measure [ 1 ], one study which examined a population-based registry of birth defects from 1983 to 2003 estimated the prevalence of ACC to be 1.8 per 10,000 births [ 2 ]. Other studies have reported the incidence of ACC as falling between 0.05% and 0.7% of the general population with a male predominance [ 3 ]. Malformations of the corpus callosum are observed in a variety of conditions that disrupt early cerebral development, including chromosomal and metabolic disorders as well as intrauterine infections and exposure to teratogens [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, the corpus callosum (CC) is predominantly affected, likely due to its central location and increased vulnerability to shear strain 6 . Importantly, the CC is involved in brain functions that are often impaired following brain injury, such as cognition, mood, and behavior 7 . A previous study found an association between younger age at first exposure to American football and later‐life microstructural alterations of the anterior CC 5 .…”
mentioning
confidence: 99%